Numerical and Experimental Investigation of Carbon Nanotube Sock Formation. (20th December 2016) - Hou, Guangfeng; Ng, Vianessa; Song, Yi; Zhang, Lu; Xu, Chenhao; Shanov, Vesselin; Mast, David; Schulz, Mark; Liu, Yijun
ABSTRACT: Formation of the carbon nanotube (CNT) sock, which is an assemblage of nanotubes in a thin cylindrical shape, is a prerequisite for continuous production of thread and sheet using the floating catalyst growth method. Although several studies have considered sock formation mechanisms, the dynamics of the sock behavior during the synthesis process are not well understood. In this work, a computational technique is utilized to explore the multiphysics environment within the nanotube reactor affecting the sock formation and structure. Specifically the flow field, temperature profile, catalyst nucleation, and residence time are investigated and their influence on the sock formation and properties are studied. We demonstrate that it is critical to control the multiphysics synthesis environment in order to form a stable sock. Sock production rate was studied experimentally and found to be linearly dependent on the amount of effective catalyst (iron in the sock) inside the reactor. To achieve a high sock production rate, the proportion of effective iron has to be high when increasing the total amount of catalyst in the reactor. Based on the analysis, we suggest that using small size catalyst and growing longer CNTs by increasing temperature, increasing residence times etc. will increase the CNT production rate and improve the properties of CNT thread/sheet produced from the sock.